What is the effect of Organizational Justice and Perceived Organizational and Supervisor Support on Employee’s Level of Trust? - Sadia Arif; Ozair Kundi; Muhammad Suleman Khan (SEISENSE Journal of Management, 2020)
Aim - Past studies support the importance of organizational justice and its impact on employees' work attitudes. There are many factors that affect the employees’ work attitude but their perceptions about organizational justice and support are significant factors. Many studies have been conducted to investigate the relationship between Organizational justice and trust but there is a lack of research to measure the mediating role of perceived support. This study examines the role of perceived support as a mediator between organizational justice and trust. Methodology - The sample of the study is 170 faculty members of public and private sector universities of Pakistan. A cross-sectional design with a standardized questionnaire is used. Findings - Results indicate that distributive, procedural and interactional justice is direct antecedents of organizational and supervisory trust with the demonstration perceived organizational support as a partial mediator between procedural justice and organizational trust. Distributive justice is related to organizational trust both directly and indirectly through perceived organizational support and supervisory trust. Finally, interactional justice is a direct and indirect predictor of supervisory trust through perceived supervisor support.